The Effect of internal migration on the colombian labor market (2007)
Internal migration in Colombia has led to demographic transformation. These migratory movements have been greatly influenced by “available” employment opportunities in different urban areas and by increased internal armed conflict. The effect of migratory flows on the probability of finding a job and income from work in Colombia’s ten main urban areas from 2001 2005 were estimated using Logit analysis and Heckman’s selection bias correction model. Evidence shows that age had a positive but decreasing incidence on the probability of being employed. Individuals with a higher level of education, male, married or cohabiting, and households with more employed members, had a greater probability of being employed. Elasticity of worked hours to produce income increased up to 2002 then decreased. Evidence also suggests that return to education is lower for migrants and forcibly-displaced population people. Moreover, the study shows that forcibly-displaced workers earn the lowest wages and face the lowest probability of finding a job.